Characterization of gaseous and semi-volatile organic compounds emitted from field burning of rice straw. (October 2015) - Kim Oanh, Nguyen Thi; Tipayarom, Aungsiri; Bich, Thuy Ly; Tipayarom, Danutawat; Simpson, Christopher D.; Hardie, David; Sally Liu, L.-J.
Abstract: Rice straw (RS) field burning, commonly practiced in Asia, produces large amounts of toxic air pollutants but has not been comprehensively characterized. This study conducted field and laboratory measurements for gaseous pollutants and semi-VOCs (16 PAHs, 16 chlorinated pesticides and 14 PCBs) in RS burning smoke to determine emission factors (EFs) and emission concentration profiles. Paddy burning experiments were done following common practices used by farmers in Southeast Asia and EFs were estimated using the carbon balance method. Laboratory hood experiments simulated burning of dry RS (moisture content ∼ 5%) and normal RS (moisture ∼ 23–30%). Semi-VOCs were analyzed separately in the particulate (PM) and gas phases, and the levels measured in smoke were compared with those in the paddy background and in general ambient air to identify enrichment of the compounds. Lower EFs of all pollutants were obtained for hood burning dry RS as compared to hood burning normal RS. EFs of all detected pollutants in the field burning were higher than hood burning. The EFs of field burning in mg kg −1 RS were 760 for benzene, 230 for toluene, 510 for SO2, 490 for NO2, 260 for total PAHs (88% in gas phase), 0.11 for total PCBs (59% in gas phase) and 0.23 for OCPs (62% in gas phase). The EF of aldehydes determined in the hood experiment was 80–150 mg kg −1 RS. As compared to ambient air, RS smoke had significant enrichment of light PAHs, fluoranthene in PM and acenaphthylene in gas phase. Smoke had a higher proportion of benzene in BTEX than roadside air. Levels of PCBs, OCPs and aldehydes were higher in the burning smoke compared to ambient air, but there was no significant enrichment of particular compounds. This study provides appropriate ranges of EFs for developing emission inventory of RS spread field burning. Highlights: Rice straw field burning was simulated using laboratory and in situ experiments. Emission factors in field burning were higher than laboratory burning. BTEX and PAHs in smoke showed distinguished profiles compared to ambient air. PCBs, OCPs, aldehydes were higher in smoke but without clear enrichment in profile. Results are relevant for current field spread burning emission in Asia.